Entrepreneurial Relations of Pakistani Entrepreneurs: A Macroeconomic and Cultural Perspective. (9th October 2015) - Pervaiz, Abeer; Khan, Mohammad Saud
This study aims at understanding entrepreneurial relations between Pakistani and Western entrepreneurs. It emphasizes the concept of national culture and tries to determine how Pakistani entrepreneurs are able to manage relations with their foreign clients in an economic downturn. The qualitative study consists of interviews conducted with various entrepreneurs of Pakistan. Political instability emerged as a major trial that most entrepreneurs faced, which in turn lead to reluctance, reliability, and trust issues among foreign investors. Despite cultural differences and economic challenges, Pakistani entrepreneurs are willing to work hard to maintain their relationships with foreign entrepreneurs.